2013
DOI: 10.4103/2229-5151.119205
|View full text |Cite
|
Sign up to set email alerts
|

A brain-dead pregnant woman with prolonged somatic support and successful neonatal outcome: A grand rounds case with a detailed review of literature and ethical considerations

Abstract: There are increased reports in the medical literature of brain death during pregnancy. In these rare cases, the decision was either to consider discontinuing homeostatic support and mechanical ventilation with an understanding that the fetus then will also die, or to continue full support in an attempt to prolong pregnancy for the purpose of maintaining the fetus alive until maturity. We report the first case in the United Arab Emirates and in literature of somatic support that extended up to 110 days with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…Pregnant women with TBF have continued to gestate pregnancies for as many as 110 days to deliver viable fetuses [13]. To continue to claim such women are dead requires a new rationale since they are biologically very much alive.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Pregnant women with TBF have continued to gestate pregnancies for as many as 110 days to deliver viable fetuses [13]. To continue to claim such women are dead requires a new rationale since they are biologically very much alive.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Brain death is a rare phenomenon (< 10% of all brain damage), and the incidence of brain death in pregnant women is even rarer. Suddaba et al determined that only 2.8% of all brain death cases occur in pregnant women (Said et al, 2013).…”
Section: Brain Death Issuesmentioning
confidence: 99%
“…There is no global register of such patients, and literature provides information on thirty-seven cases registered between 1982 and 2019. Cases of brain death in pregnant women have been reported in the United States, Finland, Italy, Germany, Switzerland, Spain, Chile, Ireland, Great Britain, Brazil, Argentina, Poland, the United Arab Emirates, Croatia, and Japan (Bush et al, 2003;Burkle et al, 2003;Esmaeilzadeh et al, 2010;Heikkinen et al, 1985;Hussein et al, 2016;Lane et al, 2004;Nishimura et al, 2016;Souza et al, 2006;Wawrzyniak et al, 2015;Woderska et al, 2012;Said, et al, 2013;Wróżyńska, 2019). It is suspected that a large number of case reports have not been published due to therapeutic failure or that no diagnosis of brain death was made due to the inability to perform full diagnostics (e.g.…”
Section: Brain Death Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the increasing number of published successful deliveries with favorable fetal outcomes does not provide firm conclusions because of the lack of published cases with unsuccessful support or unfavorable fetal outcome, consequently leading to publication bias . Leaving aside publication bias, some insights into how to manage these cases have been already cited in the literature, with successful corporeal support for 110 days as the most extended period published as a case study, and, more recently reported in the media in Brazil, 123 days . Long‐term follow up of the surviving children has been performed for 24 months in six cases, the longest being in Croatia for 36 months; however, longer follow‐ups are also needed to draw firm conclusions about the effects of such a delivery on the child.…”
Section: Introductionmentioning
confidence: 99%